An Analysis of Factors Contributing to the Choice of School ‘Informed Choice’ Vs ‘Grapevine Decision Making’ - Saluja, Anshul (JOURNAL OF INDIAN EDUCATION, 2021)
Provision of elementary education is one of the major responsibilities of the State. And with alignment to this responsibility and role, the State should endeavour to provide education to all, irrespective of any discrimination. The basic assumption behind this is that free education and incentives will attract the audience and will help achieve the objectives of Universal Elementary Education (UEE). Over the years, the access to schooling provisions has been increased by increasing the resource base and number of government-run schools. Several studies have shown that despite free provision of education, the households increasingly prefer private unaided schools by utilising their limited resources to fulfil ‘that’ need which the government is already legally bound to provide. While exercising their choices explicitly, they are seeking the options that relate to their own needs and interests. This paper is based on a survey of randomly selected 7 villages of Faridabad district of Haryana and tried to develop insights as to why parents choose a particular school and detearminants for making these choices to develop an understanding of the process and whether they form an informed opinion or are merely perception based, twenty-one schools were taken under the framework of investigation.